2020
DOI: 10.1097/md.0000000000020461
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for diabetic gastroparesis

Abstract: Background: Diabetic gastroparesis (DG) is a common autonomic neuropathy which impacts on nutritional state and quality of life in diabetic patients, and it also adversely affects glycemic control in diabetes. The prevalence of DG is growing with the number of patients with diabetes continues to increase. However, there is no definitive answer as to which of the current therapies is the best for the clinical treatment of the different manifestations of DG. The subject of this study is to answer the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Dietary interventions (including changes in dietary composition, size, and frequency of consumption, etc.) and stable blood sugar control are the fundamental management methods for DGP ( 7 , 55 ). Dietary interventions can improve gastroparesis symptoms by regulating blood sugar control and promoting gastric emptying in DGP patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary interventions (including changes in dietary composition, size, and frequency of consumption, etc.) and stable blood sugar control are the fundamental management methods for DGP ( 7 , 55 ). Dietary interventions can improve gastroparesis symptoms by regulating blood sugar control and promoting gastric emptying in DGP patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the treatment of DGP includes drug therapy, gastric electrical stimulation, endoscopic therapy, surgical treatment, and dietary therapy, all of which can improve gastric emptying ( 7 ). However, clinicians mainly focus on gastric prokinetic drugs for the treatment of DGP, such as domperidone, metoclopramide, and mosapride citrate ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The finding showed SMD to HC of 15.75min in DM and 7.46-min in DG, with longer GE50 in DM, contrary to the definition of DG itself, which is an established diagnosis after findings of definite prolonged gastric emptying with the absence of structural obstruction. 54 The longer GE50 in DM is because studies included in the meta-analysis in DG used a liquid test-meal, 12,39 while all samples in DM were measured with a solid test-meal, which requires a longer time to digest. 26,34,38 Therefore, a slower half-emptying time was found in the solid meal test in DM compared to liquid test in DG populations.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, abdominal pain is increasingly recognized as one of the most common symptoms of this disease [8] . Diabetes is the most frequent cause of gastroparesis, approximately one-third of diabetic patients suffer from DGP [9,10] . Consequently, as the number of diabetes continues to grow, the number of patients with DGP is increasing as well [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is the most frequent cause of gastroparesis, approximately one-third of diabetic patients suffer from DGP [9,10] . Consequently, as the number of diabetes continues to grow, the number of patients with DGP is increasing as well [10] . It has been reported that DGP is much more common in type 1 diabetes mellitus (T1DM) than in type 2 diabetes mellitus (T2DM) [11] .…”
Section: Introductionmentioning
confidence: 99%